Are the effects of terrorism short-lived? - Vincenzo Bove; Georgios Efthyvoulou; Harry Pickard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Numerous studies demonstrate that terrorism causes strong public reactions immediately after the attack, with important implications for democratic institutions and individual well-being. Yet, are these effects short-lived? We answer this question using a quasi-experimental design and data on three successful and three foiled terrorist attacks in the United Kingdom. We find that heightened risk perceptions and emotional reactions in the wake of successful attacks do not dissipate in the very short run but are sustained over time and up to 130 days after the attacks. We also find that, whereas large-scale attacks cause a long-lasting shift in risk assessments and emotions, the corresponding effect of smaller-scale terrorism incidents appears to subside within one month. Interestingly, foiled attacks can also affect public perceptions, which, however, quickly return to normal levels. We argue that the extent of media coverage is partly responsible for the duration of these effects.
Keywords: 330; terrorism; risk perceptions; emotions; long-term consequences; quasi-experimental design